CanWalk: a feasibility study with embedded randomised controlled trial pilot of a walking intervention for people with recurrent or metastatic cancer. Issue 2 (15th February 2017) - Tsianakas, Vicki; Harris, Jenny; Ream, Emma; Van Hemelrijck, Mieke; Purushotham, Arnie; Mucci, Lorelei; Green, James S A; Fewster, Jacquetta; Armes, Jo
Abstract : Objectives: Walking is an adaptable, inexpensive and accessible form of physical activity. However, its impact on quality of life (QoL) and symptom severity in people with advanced cancer is unknown. This study aimed to assess the feasibility and acceptability of a randomised controlled trial (RCT) of a community-based walking intervention to enhance QoL in people with recurrent/metastatic cancer. Design: We used a mixed-methods design comprising a 2-centre RCT and nested qualitative interviews. Participants: Patients with advanced breast, prostate, gynaecological or haematological cancers randomised 1:1 between intervention and usual care. Intervention: The intervention comprised Macmillan's 'Move More' information, a short motivational interview with a recommendation to walk for at least 30 min on alternate days and attend a volunteer-led group walk weekly. Outcomes: We assessed feasibility and acceptability of the intervention and RCT by evaluating study processes (rates of recruitment, consent, retention, adherence and adverse events), and using end-of-study questionnaires and qualitative interviews. Patient-reported outcome measures (PROMs) assessing QoL, activity, fatigue, mood and self-efficacy were completed at baseline and 6, 12 and 24 weeks. Results: We recruited 42 (38%) eligible participants. Recruitment was lower than anticipated (goal n=60), the most commonly reported reason being unable to commit to walking groups (n=19). Randomisation procedures worked well with groups evenly matched for age, sex and activity. By week 24, there was a 45% attrition rate. Most PROMs while acceptable were not sensitive to change and did not capture key benefits. Conclusions: The intervention was acceptable, well tolerated and the study design was judged acceptable and feasible. Results are encouraging and demonstrate that exercise was popular and conveyed benefit to participants. Consequently, an effectiveness RCT is warranted, with some modifications to the intervention to include greater tailoring and more appropriate PROMs selected. Trial registration number: ISRCTN42072606 .